Modélisation et commande d’une MADA dans un système éolien utilisant une stratégie MPPT - TAMMA Oussama; HECHIFA Yahia; DJABER Yacine (Université Echahid Hama Lakhdar- Eloued, 2025)
This thesis focuses on the modeling and control of Doubly-Fed Induction Generators (DFIG) within wind energy conversion systems, using a Maximum Power Point Tracking (MPPT) strategy to enhance power extraction. provides a comprehensive review of wind energy conversion systems, their architectures, and the generator types commonly used. discusses the aerodynamic and mechanical modeling of the wind turbine, followed by the implementation of an MPPT control algorithm to improve efficiency under variable wind conditions. presents the dynamic modeling of the DFIG based on the dq reference frame equations. investigates vector control techniques for the DFIG, aiming for decoupled flux and torquecontrol, while maintaining overall system stability and performance. تركز هذه الأطروحة على نمذجة وتحكم مولدات الحث ثنائية التغذية (DFIG) ضمن أنظمة تحويل طاقة الرياح، باستخدام استراتيجية تتبع نقطة القدرة القصوى (MPPT) لتحسين استخلاص الطاقة. تقدم مراجعة شاملة لأنظمة تحويل طاقة الرياح، وبنياتها، وأنواع المولدات الشائعة الاستخدام. تناقش النمذجة الديناميكية الهوائية والميكانيكية لتوربينات الرياح، متبوعةً بتطبيق خوارزمية تحكم MPPT لتحسين الكفاءة في ظل ظروف الرياح المتغيرة. تقدم النمذجة الديناميكية لمولدات الحث ثنائية التغذية (DFIG) استنادًا إلى معادلات الإطار المرجعي dq. تبحث في تقنيات التحكم في المتجهات لمولدات الحث ثنائية التغذية (DFIG)، بهدف التحكم في التدفق وعزم الدوران المنفصلين، مع الحفاظ على استقرار النظام وأدائه بشكل عام.
Master's thesis in electromechanics.2025
Keywords: L'énergie éolienne; système éolien; stratégie MPPT; MADA